School Funding Formulas Review of Main Characteristics and Impacts - Fazekas, Mihály (OECD Publishing, 2012)
This study provides a literature review on school funding formulas across OECD countries. It looks at three salient questions from a comparative perspective: i) What kind of school formula funding schemes exist and how are they used, particularly for promoting the needs of socially disadvantaged pupils?; ii) How do school formula funding regimes perform according to equity and efficiency standards?; iii) What are the unresolved issues? Formula funding of schools, as opposed to administrative discretion and bidding, relies on a mathematical formula containing a number of variables (e.g. number of pupils), each of which has attached to it a cash amount to determine school budgets. Across OECD countries there are four main groups of variables in such formulas: i) student number and grade level-based; ii) needs-based; iii) curriculum or educational programme-based and; iv) school characteristics-based. Sometimes output and outcome-related variables are also used.
Keywords: Education